Gideon Falls. Volume 3, Stations of the cross - Lemire, Jeff (Image Comics, Inc., 2019)
After the mind-blowing events of the second arc, our story heads right through the looking glass. Father Burke tracks a vicious killer named...Norton Sinclair? And when that killer can travel through time (and space!) readers are in for a wild ride.